Implementasi Konsep Industri Strategis dalam Pengembangan Industri Pengolahan Perikanan - Nur Abdillah; Ihsan Ihsan; Abdul Rachman Rasyid (Jurnal Wilayah & Kota Maritim (Journal of Regional and Maritime City Studies), 2019)
The fisheries sector has an important role in improving the economy of the region with great potential from marine waters. However, the development of the fisheries sector is still not a priority and has received attention in Takalar District. Activities from the fisheries sector are only at the distribution stage of raw materials so that only the value of the production sector is not value added. The purpose of this study was to identify the potential of the region and the characteristics of the fisheries processing industry and the direction in the development of the fisheries processing industry in Takalar District. This study uses secondary data with quantitative and qualitative approaches that use sectoral contribution analysis, location quotient analysis, priority plus index, spatial analysis, SWOT analysis with AHP and descriptive analysis. The results of this study included 63 superior commodities, the highest sector contribution of 30.2% in South Galesong and 5 priority commodities. Identified characteristics of fisheries processing industry in terms of potential fisheries resources are less fulfilling, aspects of human resources have potential, infrastructure aspects are adequate in supporting the development of processing industries, and the supporting facilities have not been as large as 37 units. 13 strategies were identified for the development of the fisheries processing industry in Takalar District with the implementation of the linear concept and determined the first growth center (growth pole) in North Galesong (North Takalar) and the second growth center in Mangarabombang (South Takalar).